PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN ORANG TUA BALITA TENTANG PNEUMONIA DI WILAYAH KOTA PADANG TAHUN 2018 - Annisa Novita Sary; Edison Edison; Oktariyani Dasril (Ensiklopedia of Journal, 2019)
Upper respiratory tract infections (ARI), especially pneumonia, are still the main diseases that cause infant and toddler mortality and illness. The incidence of ARI deaths (especially pneumonia) in the 12-23 month age group was 21.7%. The high incidence and mortality due to pneumonia in infants is caused by various factors, one of which is the factor of knowledge and smoking behavior of parents. The proportion of smoking behavior in Indonesia increased from 34.2% (2007) to 36.3% (2013). Research objectives: 1) To study the effect of health education on changes in smoking behavior in the incidence of childhood pneumonia. This type of research is experimental research with Quasi experimental design (quasi-experimental) with the design of One Group Pretest Postest. The experimental group in this study was given health education by providing counseling using leaflet media and brochures. The population in this study were all parents who had children aged 12-59 months at the Padang City Health Center. The number of samples is 124 people. Data were analyzed by univariate and bivariate. Research is conducted on parents who have toddlers under five through observation and questionnaires using accidental sampling techniques. Based on research that has been carried out until July 2018 on 124 samples, it can be concluded that there were 32 cases of pneumonia in infants. Found more than half of the 105 respondents (84.7%) had smoking behavior. Where as many as 58.9% of family members have smoking behavior in the heavy category. After being given health education there was a change that was as much as 72.6% of family members who had children under five in the city of Padang had smoking behavior in the light category. From the results of statistical tests, it was found that health education was effective in changing the smoking behavior of family members (p-value = 0.001) on the incidence of pneumonia of children under five from those who had severe smoking.